2002
DOI: 10.1063/1.1519841
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond excitation tuning and site energy memory of population transfer in poly(p-phenylenevinylene): Gated luminescence experiments and simulation

Abstract: We present a comprehensive experimental and computational study on fs-relaxational dynamics of optical excitations in the conjugated polymer poly(p-phenylenevinylene) (PPV) under selective excitation tuning conditions into the long-wavelength, low-vibrational S1ν=0-density-of-states (DOS). The dependence of single-wavelength luminescence kinetics and time-windowed spectral transients on distinct, initial excitation boundaries at 1.4 K and at room temperature was measured applying the luminescence up-conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…In principle, higher energy excitation should lead to the initial formation of higher energy excitons, which have more probability to hop to lower energy localized states, so that exciton hopping in P3HT could be affected by the excitation wavelength, as was reported for the PPV polymer. 90 Judging from the normalized emission spectra, the spectral changes and time constants associated with exciton hopping are, however, quite independent of 400 or 500 nm excitation in solution. The wavelengthdependent spectral rise that we observe 1À2 ps after photoexcitation might have a contribution from the population of more red-shifted states by hopping.…”
Section: 49à51mentioning
confidence: 99%
“…In principle, higher energy excitation should lead to the initial formation of higher energy excitons, which have more probability to hop to lower energy localized states, so that exciton hopping in P3HT could be affected by the excitation wavelength, as was reported for the PPV polymer. 90 Judging from the normalized emission spectra, the spectral changes and time constants associated with exciton hopping are, however, quite independent of 400 or 500 nm excitation in solution. The wavelengthdependent spectral rise that we observe 1À2 ps after photoexcitation might have a contribution from the population of more red-shifted states by hopping.…”
Section: 49à51mentioning
confidence: 99%
“…[64,65] This is clearly much less than the typical length scale of about 10-20 nm in optimized bulk heterojunctions, estimated by structural characterization in optimized morphologies. [27][28][29][30][31][32] Furthermore, point-like exciton diffusion by the hopping mechanism has been measured on numerous occasions to take 0.5-1 ps for a single hopping step, [39][40][41][42][44][45][46][49][50][51]88,89] which is again too slow to explain how excitons reach a fullerene interface in <100 fs. In agreement with this, an ultrafast transient absorption study of poly[2,7-(9,9-dioctylfluorene)-alt-5,5-(4,7′-di-2-thienyl-2′,1′,3-benzothiadiazole)] (APFO3) films with various concentrations studies on pristine polymers in our group, we have pointed out that the ultrafast charge separation can compete with relaxation processes such as excited-state localization and exciton diffusion.…”
Section: Photoexcitation and Charge Transfermentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Charge transfer at the donor/acceptor interface splits the excitation into a domain-segregated electron and hole. Many time-resolved studies have shown that the charge transfer to the fullerene materials is nearly quantitative and ultrafast (<100 fs for many optimized systems).…”
Section: Introductionmentioning
confidence: 99%
“…At longer times, λ ex has no influence on the dynamics of exciton hopping, although such an effect might be expected since selective excitation of low energy sites prevents further downhill relaxation. 36 Most probably, our quite broadband femtosecond laser excitation always leads to some inhomogeneity in excited chromophores. Finally, the results show that neither the exciton decay nor the yield of long-lived states depends on λ ex .…”
Section: ■ Introductionmentioning
confidence: 99%